Effects of Cover Crops and Phosphorus Fertilizer Management on Soil Health Parameters in a No-Till Corn-Soybean Cropping System in Riley County, Kansas - L. M. Starr; P. J. Tomlinson; N. O. Nelson; C. L. Stewart; K. L. Roozeboom; G. J. Kluitenberg; D. R. Presley (Kansas Agricultural Experiment Station Research Reports, 2019)
This study was implemented to examine the effects of cover crops and mineral phosphorus (P) fertilizer application on water quality and soil health parameters. The experiment was established in 2014, at the Kansas Agricultural Watershed (KAW) field research facility, Ashland Bottoms Research Farm, Kansas State University, Manhattan, KS. The experiment was a 2 × 3 factorial design with two cover crop treatments (with and without) and three phosphorus fertilizer treatments (none, spring injected P, and fall broadcast P). Measures of nutrient demand (enzyme activity), microbial metabolic activity (soil respiration), and labile carbon (potassium permanganate oxidized carbon) were taken to assess the treatment effects on the nutrient status and relative microbial activity of the soil ecosystem. Results from spring 2018 showed a cover crop main effect for five enzymes (acid and alkaline phosphatase, phosphodiesterase, β-glucosidase, and β-glucosaminidase), soil respiration, and active carbon (C). The main fertilizer effect was in potential β-glucosaminidase activity (P= 0.02). There was an interaction effect between phosphorus fertilizer and cover crop for the enzyme arylsufatase.
Keywords: soil health; cover crop; enzymes; microbial activity